Human dirofilariasis due to Dirofilaria repens in southern India - Kotigadde, Subbannayya (Medknow Publications & Media Pvt Ltd, 2012)
Dirofilariasis is primarily confined to animals such as dogs, cats, foxes and raccoons. Human dirofilariasis is an accidental zoonotic infection acquired through mosquitoes. Human dirofilariasis due to Dirofilaria repens though endemic in Kerala, reports from Karnataka state are rare. We report a case of solitary subcutaneous dirofilariasis of the eyelid due to D. repens in a 47-year-old woman. She presented with periorbital edema. The swelling was soft, cystic with associated tenderness. A thin, white worm was noticed in the lesion and was removed by traction which was subsequently identified to be D. repens.